IMPROVING STUDENTS' HANDS ONLY CPR SKILLS THROUGH BLS SIMULATION ACTIVITIES: A PRE-EXPERIMENTAL STUDY AT KHOMSANI NUR BOARDING SCHOOL IN LUMAJANG - Syaifuddin Kurnianto; Arista Maisyaroh; Eko Prasetya Widianto (UPT Penerbitan Universitas Jember, 2023)
Background: Out-of-Hospital Cardiac Arrest (OHCA) or better known as cardiac arrest is the leading cause of death in emergency cases. Quality Cardiopulmonary Resuscitation (CPR) is by performing compression and ventilation so as to help victims of cardiac arrest to survive. But many people do not know about the procedure for giving CPR to victims of cardiac arrest. The purpose of this study is to increase the knowledge of santri as part of the community about the proper and correct CPR procedures. Translated with www.DeepL.com/Translator (free version). Methods: The research method used preexperimental with pre post test approach. The population of this research is the students of Khomsani Nur Lumajang boarding school, totaling 37 people.. Results: Data analysis used the Wilcoxon signed rank test. As a result, hands only CPR training has a positive effect on the knowledge and skills of students in performing CPR with a p-value of 0.0001. The average score before the hands only CPR simulation with a minimum score of 20 and a maximum score of 75, and the average score after the hands only CPR simulation with a minimum score of 75 and a maximum score of 100, it can be seen that there is an increase in respondents about Hands Only CPR. This shows that there is a relationship between education or training and the level of knowledge of respondents.. Conclusions: Hands only CPR training can improve the knowledge and skills of students in providing assistance using hands only CPR to victims of cardiac arrest emergencies.